2002
DOI: 10.1002/polb.10222
|View full text |Cite
|
Sign up to set email alerts
|

Lamellar morphology and equilibrium melting temperature of syndiotactic polystyrene in β‐crystalline form

Abstract: Lamellar morphology and thickness of syndiotactic polystyrene (sPS) samples melt-crystallized at various temperatures were probed using transmission electron microscopy (TEM) and small-angle X-ray scattering (SAXS). In addition, the melting temperature and enthalpy of the crystallized samples were characterized with differential scanning calorimetry. Under appropriate thermal treatments, all the samples investigated in this study were crystallized into ␤Ј crystal modification, as revealed by wide-angle X-ray d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…In a sPS/aPS blend, the equilibrium melting temperature of the blend ($T'_{\rm m}$ ) will be depressed due to the presence of aPS diluents. As the applicability of the Hoffman‐Weeks (or Gibbs‐Thomson) plot to determine $T'_{\rm m}$ of the blends was expected to be limited under certain circumstances,17,18 theoretical $T'_{\rm m}$ values were estimated in this work. According to Flory‐Huggins theory,19 the $T'_{\rm m}$ of a crystalline polymer in miscible crystalline/amorphous blends is estimated on the basis of the Nishi‐Wang expression,20 as given in Equation (2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a sPS/aPS blend, the equilibrium melting temperature of the blend ($T'_{\rm m}$ ) will be depressed due to the presence of aPS diluents. As the applicability of the Hoffman‐Weeks (or Gibbs‐Thomson) plot to determine $T'_{\rm m}$ of the blends was expected to be limited under certain circumstances,17,18 theoretical $T'_{\rm m}$ values were estimated in this work. According to Flory‐Huggins theory,19 the $T'_{\rm m}$ of a crystalline polymer in miscible crystalline/amorphous blends is estimated on the basis of the Nishi‐Wang expression,20 as given in Equation (2).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that the respective T m0 for α ‐ and β ‐form sPS is ca. 281 and 291 °C, obtained from linear Hoffman‐Weeks plots 17,18. Based on Equation (2), $T'_{\rm m}$ of the blends can be deduced and plotted in Figure 4 as a function of aPS content after substituting the following parameters: V 1 = 99.0 cm 3 · mol −1 , V 2 = 92.9 cm 3 · mol −1 ,21,22 N 2 = 1 924 and N 1 = 12.5, 40.4 and 962 for aPS(L), aPS(M) and aPS(H), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the annealing process favors the formation of crystalline forms within the polymer, as testified by the appearance of secondary peaks (additional information on identification of the characteristic peaks can be found in refs. [21][22][23][24]. Note that the crystalline form corresponding to the peak at 2 ϭ 5.0°-7.5°, which also was present in the neat polymer (but only after the annealing process), was strongly enhanced by the presence of the nanofiller, as the peak was present in the nanocomposite even before the annealing process (and did not seem to depend on the thermal history of the material).…”
Section: Wide-angle X-ray Diffractometrymentioning
confidence: 87%
“…As pointed out by Alamo et al [39], if the experimental T m is measured at very low levels of crystallinity (where the thickening effect of lamellae is greatly limited), the conventional HW plot is applicable in determining the T 0 m : Therefore, despite the arguments, the HW plot is still commonly used to date. Also, we want to mention that the T 0 m value we determined for pure sPS is close to the value ð292:7^2:7 8CÞ determined based on the TEM results combined with the Gibbs -Thomson equation [40].…”
Section: Melting Behaviormentioning
confidence: 89%